Manchester Ship Canal Back to the Future for Disused European Waterways - Hisham Elkadi, Sara Biscaya (KIT Scientific Publishing, 2021)
This book investigates how urban/rural patterns provide differing conditions for living and working. The project is to read and analyse these urban/rural settlement structures and provide insight into the patterns of living and working that have formed them and possible development of a smart networked metropole that integrate the urban and rural socio-economic and physical infrastructures for the future of disused European waterways.